Diagnostic accuracy of salivary gland ultrasonography with different scoring systems in Sjögren's syndrome: a systematic review and meta-analysis. Issue 1 (December 2018) - Zhou, Mingzhu; Song, Shuju; Wu, Shanshan; Duan, Ting; Chen, Letian; Ye, Jingyi; Xiao, Jun
Abstract Noninvasive objective salivary gland ultrasonography (SGU) had been widely used to evaluate major salivary gland involvement in primary Sjögren's syndrome (pSS) and treatment responses. However, the evaluation score, diagnostic sensitivity, and diagnostic specificity significantly varied among clinical studies. We conducted this meta-analysis to assess the diagnostic accuracy of different SGU scoring systems using the American-European Consensus Group criteria. Of the 1301 articles retrieved from six databases, 24 met the criteria for quality assessment and 14 for meta-analyses. The pooled sensitivities were 75% (0–4) with I2 = 92.0%, 84% (0–16) with I2 = 63.6%, and 75% (0–48) with I2 = 90.9%; the pooled specificities were 93% (0–4) with I2 = 71.5%, 88% (0–16) with I2 = 65.4%, and 95% (0–48) with I2 = 83.9%; the pooled diagnostic odds ratios were 71.26 (0–4) with I2 = 0%, 46.3 (0–16) with I2 = 73.8%, and 66.07 (0–48) I2 = 0%; the areas under the SROC curves were 0.95 (0–4), 0.93 (0–16), and 0.94 (0–48). These results indicated that the 0–4 scoring system has a higher specificity and a less heterogeneity than other systems, and could be used as a universal SGU diagnostic standard.